Miniaturized Backward Coupler Realized by the Circuit‐Based Planar Hyperbolic Waveguide - Zhiwei Guo; Juan Song; Haitao Jiang; Hong Chen (Advanced Photonics Research, 2021)
Planar waveguides limit the transmission of electromagnetic waves in a specific direction and have a wide range of applications in filters, sensors, and energy‐transfer devices. However, given the increasing demand for planar‐integrated photonics, new waveguides are required with excellent characteristics such as more functionality, greater efficiency, and smaller size. Herein, the experimental results for a planar microwave‐regime waveguide fabricated from circuit‐based magnetic hyperbolic metamaterial (HMM) are reported. HMM is a special type of anisotropic metamaterial, whose isofrequency contour (IFC) takes the form of an open hyperboloid. Because of the open‐dispersion IFCs, HMMs support propagating high‐k modes with large effective refractive indices, which allow planar hyperbolic waveguides to be miniaturized. Especially, as opposed to the traditional dielectric slab waveguide, the group velocity and phase velocity in hyperbolic waveguides are oriented in opposite directions—a characteristic that is exploited to realize the backward propagation of electromagnetic waves. Based on this property, a backward coupler based on the hyperbolic waveguide is designed and experimented with. Herein, the significant potential of circuit‐based platforms for the experimental study of the propagation and coupling of guided modes is not only revealed but also the use of HMMs for numerous integrated functional devices is promoted.